2022
DOI: 10.1093/brain/awac234
|View full text |Cite
|
Sign up to set email alerts
|

Towards network-guided neuromodulation for epilepsy

Abstract: Epilepsy is well-recognized as a disorder of brain networks. There is a growing body of research to identify critical nodes within dynamic epileptic networks with the aim to target therapies that halt the onset and propagation of seizures. In parallel, intracranial neuromodulation, including deep brain stimulation and responsive neurostimulation, are well-established and expanding as therapies to reduce seizures in adults with focal epilepsy; and there is emerging evidence for their efficacy in children and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 194 publications
4
60
0
Order By: Relevance
“…Moreover, our previous study made the first attempt to characterize the dynamic effective connectivity (DEC) in the DMN of patients with JME, demonstrating that the DEC between brain networks is very important in JME [ 20 ]. Epilepsy is regarded as a disruption of functional networks [ 21 ], and an increasing number of studies have suggested that cerebro-cerebellar interactions are important for the induction of JME [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our previous study made the first attempt to characterize the dynamic effective connectivity (DEC) in the DMN of patients with JME, demonstrating that the DEC between brain networks is very important in JME [ 20 ]. Epilepsy is regarded as a disruption of functional networks [ 21 ], and an increasing number of studies have suggested that cerebro-cerebellar interactions are important for the induction of JME [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results offer a potentially more effective strategy and/or new anatomical targets for therapeutic interventions for memory and cognitive deficits. In contrast to the widespread dispersed cortical networks, the thalamic nuclei connected to these networks are compact and condensed in confined volumes of neural tissue, making them suitable for local interventions like DBS to effectively modulate larger thalamocortical networks (65) . Future studies will determine the exact role of the ANT theta activities in memory and cognitive functions, employing closed-loop and long-term adaptive stimulation paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that different thalamic sites are involved differently in the very early stage of seizure propagation. This agrees with the extant literature, where thalamic participation in the epileptogenic networks of focal epilepsies has been documented (Ilyas et al ., 2022; Piper et al .,2022). Pioneering past studies have shown increased synchrony between cortical and thalamic ictal activity in temporal lobe seizures, and that in a majority of cases the thalamic activity was driven by cortical activity (Guye et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%